Diversity and phylogenetic relationships of Glossina populations in Nigeria and the Cameroonian border region - Shaida, Stephen Saikiu; Weber, Judith Sophie; Gbem, Thaddeus Terlumun; Ngomtcho, Sen Claudine Henriette; Musa, Usman Baba; Achukwi, Mbunkha Daniel; Mamman, Mohammed; Ndams, Iliya Shehu; Nok, Jonathan Andrew; Kelm, Soerge (BMC microbiology, 2018)
Background Tsetse flies are vectors of trypanosomes, parasites that cause devastating disease in humans and livestock. In the course of vector control programmes it is necessary to know about the Glossina species present in the study area, the population dynamics and the genetic exchange between tsetse fly populations. Results To achieve an overview of the tsetse fly diversity in Nigeria and at the Nigeria-Cameroon border, tsetse flies were trapped and collected between February and March 2014 and December 2016. Species diversity was determined morphologically and by analysis of Cytochrome C Oxidase SU1 (COI) gene sequences. Internal transcribed spacer-1 (ITS-1) sequences were compared to analyse variations within populations. The most dominant species were G. m. submorsitans , G. tachinoides and G. p. palpalis . In Yankari Game Reserve and Kainji Lake National Park, G. submorsitans and G. tachinoides were most frequent, whereas in Old Oyo National Park and Ijah Gwari G. p. palpalis was the dominant species. Interestingly, four unidentified species were recorded during the survey, for which no information on COI or ITS-1 sequences exists. G. p. palpalis populations showed a segregation in two clusters along the Cameroon-Nigerian border. Conclusions The improved understanding of the tsetse populations in Nigeria will support decisions on the scale in which vector control is likely to be more effective. In order to understand in more detail how isolated these populations are, it is recommended that further studies on gene flow be carried out using other markers, including microsatellites.